CTNI-40. PHASE I TRIAL OF SULFASALAZINE COMBINED WITH STEREOTACTIC RADIOSURGERY FOR RECURRENT GLIOBLASTOMA: STUDY PROTOCOL FOR NCT04205357. (14th November 2022) - Skeie, Bente Sandvei; Bragstad, Sidsel; Sarowar, Shahin; Behbahani, Maziar; Filippi, Christopher; Knisely, Jonathan; Schulder, Michael; Goplen, Dorota; Eide, Geir Egil; Heggdal, Jan Ingemann; Gruner, Renate; Enger, Per Øyvind
Abstract: Glioblastoma (GBM) is one of the most aggressive, radioresistant types of cancer with a dismal prognosis. Sulfasalazine (SAS) has shown tumor selective radiosensitizing properties in preclinical studies. The antioxidant glutathione (GSH) produced at high levels in glioma cells normally protects against radiation injury by scavenging reactive oxygen species produced during radiation therapy (RT). SAS blocks cysteine uptake through the x CT-channel, a rate-limiting step for GSH production. We have previously shown slowing of tumor growth and prolonged survival when SAS was combined with stereotactic radiosurgery (SRS) in vivo compared to either treatment alone. Our hypothesis is that SAS potentiates the efficacy of SRS for recurrent GBM with a low risk of adverse events (AE). The primary end-point is to establish the recommended dose for efficacy testing in phase II/III trials. This phase 1 dose-escalation trial utilizes a standard 3 + 3 design with 3-6 patients per cohort. Patients will be treated with oral SAS (1.5, 3.0, 4.5 or 6.0 g/day) 3 days prior to single session SRS. The SAS-dose will be escalated depending on the absence/presence of toxicity in the previous cohort of treated patients. If more than 1 of 3-6 patients ( ≥ 33 %) is experiencing grade 3 or higher toxicity levels, the study will be terminated. The dose below will be the recommended dose. Toxicity is graded using the Common Toxicity Criteria for Adverse Events (CTCAE) v5.0 recorded the first 30 days. Secondary end-points are assessments of 1) intratumoral GSH production (GSH-spectroscopy), 2) late AE utilizing 11C-MET-MRI-PET 3) changes in KPS/quality of life (FACT-Br), 4) need for steroidal treatment, 5) progression free and overall survival. Novel treatment modalities are urgently needed. This trial will establish the recommended dose for SAS repurposed as a radiosensitizer for a future phase 2/3 trial and may ultimately lead to improvement of current GBM treatment.